PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM DI MUSIM PANDEMI - Muhammad Mustakim (Universitas Nahdlatul Ulama Sidoarjo, 2021)
This study aims to 1). To know the effect of financial performance on farmasi Sector registered in Indonesia Stock Exchange period 2020 simultaneously, 2). Determine the effect of financial performance on farmasi farmasi Sectors which is listed on Indonesia Stock Exchange period 2020 partially. Population used in this research is amounting to 9 companies. The method used in this research is multiple linear regression analysis. Based on the results of the research, the first hypothesis test shows the financial performance simultaneously have no significant effect on the dependent variable Price Stock of 79.2%. The results of the second hypothesis test show that the independent variables of Return On Asset, Earning Per Share and Debt to Equity Ratio have no a significant effect partially on Stock Pric, Just has Return On Equity a positive effect and significant.